"Disrupt and induce" intermolecular interactions to rationally design organic semiconductor crystals: from herringbone to rubrene-like pitched π-stacking. Issue 6 (7th January 2020) - Wang, Chengyuan; Hashizume, Daisuke; Nakano, Masahiro; Ogaki, Takuya; Takenaka, Hiroyuki; Kawabata, Kohsuke; Takimiya, Kazuo
Abstract : The rational design of organic semiconductor crystals is realized by β-methylthionation of acenedithiophenes through manipulating intermolecular interactions in a "disrupt and induce" manner. Abstract : The packing structures of organic semiconductors in the solid state play critical roles in determining the performances of their optoelectronic devices, such as organic field-effect transistors (OFETs). It is a formidable challenge to rationally design molecular packing in the solid state owing to the difficulty of controlling intermolecular interactions. Here we report a unique materials design strategy based on the β-methylthionation of acenedithiophenes to generally and selectively control the packing structures of materials to create organic semiconductors rivalling rubrene, a benchmark high-mobility material with a characteristic pitched π-stacking structure in the solid state. Furthermore, the effect of the β-methylthionation on the packing structure was analyzed by Hirshfeld surface analysis together with theoretical calculations based on symmetry-adapted perturbation theory (SAPT). The results clearly demonstrated that the β-methylthionation of acenedithiophenes can universally alter the intermolecular interactions by disrupting the favorable edge-to-face manner in the parent acenedithiophenes and simultaneously inducing face-to-face and end-to-face interactions in the β-methylthionated acenedithiophenes. This "disrupt and induce" strategy to manipulate intermolecular interactions can open a door to rational packing design based on the molecular structure.